23.5k views
4 votes
Sole the equation. check your solution 2.5 y + 6=4.5y-1 ​

User Ian Zane
by
5.9k points

2 Answers

0 votes

Answer:

3.5 = y

Explanation:

2.5y + 6 = 4.5y - 1

2.5y + 7 = 4.5y

7 = 2y

3.5 = y

Check:

2.5y + 6 = 4.5y - 1

2.5(3.5) + 6 = 4.5(3.5) - 1

2.5(3.5) + 7 = 4.5(3.5)

8.75 + 7 = 15.75

15.75 = 15.75

User AwesomeHunter
by
5.6k points
4 votes

Answer:


y=3.5

Explanation:


2.5y+6=4.5y-1

Start by subtracting
6 from both sides of the equation:


2.5y=4.5y-7

Subtract
4.5y from both sides of the equation:


-2y=-7

Divide both sides of the equation by the coefficient of
y, which is
-2:


y=3.5

_

Check your solution by substituting the solved value of
y (
3.5) into the initial equation:


2.5(3.5)+6=4.5(3.5)-1


8.75+6=15.75-1


14.75=14.75

Since both sides of the equation are equal to each other, our solution is correct!

User Adrilz
by
5.6k points